PENGARUH MANAJEMEN PERUBAHAN, ORGANISASI PEMBELAJARAN, BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI BAGIAN ORGANISASI SEKRETARIAT DAERAH KOTA SAWAHLUNTO - Rona Astria; Heliyani Heliyani (Institut Agama Islam Negeri Kerinci, 2022)
Purpose: This study aims to see the effect of Change management, Organizational learning Organizational Culture and Work motivation on employee performance in the Organizational Section of the Regional Secretariat of Sawahlunto City. Design/methodology/approach: The population in this study were all employees in the Organizational Section of the Regional Secretariat of Sawahlunto City as many as 32 people. And the technique of determining the number of samples taken as respondents The number of samples taken as respondents using the Slovin formula. Findings: The results of this study indicate that Change management, learning organizations ,Organizational culture and Work motivation has a positive effect on employee performance in the Organizational Section of the Regional Secretariat of Sawahlunto City. then Change management, organizational learning and organizational culture and work motivation together have a positive effect on employee performance at the Organizational Section of the Sawahlunto City Secretariat. Research implications: The results of the study concluded that to improve the performance of employees the Organizational Section of the Regional Secretariat of Sawahlunto City it was expected that employees would maintain and increase motivation and try to adjust and follow all policies at work.